The effect of higher-order extended uncertainty principle on the black hole thermodynamics. (11th August 2021) - Hamil, B.; Lütfüoğlu, B. C.
Abstract: In this paper, we consider a new form of the extended uncertainty principle (NEUP) and we study the Unruh temperature and black hole's thermodynamic properties. At first, we give a brief introduction of the NEUP and show the existence of the minimal uncertainty value in momentum. Then, by using the NEUP in a heuristic recipe, we compute corrections to the Unruh temperature and compare with the usual case. Then, we study the Schwarzschild black hole thermodynamics by following NEUP. We derive an expression of the corrected mass-temperature, heat capacity and entropy functions. For all cases, we enrich our examination with graphical analysis as well as their comparisons.